(untitled) (Applied Biological Research, 2017)
Molecular characterization of 48 genotypes of gladiolus was carried out using PCR based ISSR technique. A total number of 239 loci were generated out of which 216 loci ranging in size of 200 to 1000 bps were found polymorphic (90.38% polymorphic bands). The PIC value of primers ranged from 0 to 0.22 with mean value of 0.15 primer-1 and most informative marker was related to UBC 853 followed by UBC 859. Based on banding pattern, the cluster analysis was done using UPGMA and dendrogram was constructed. The similarity coefficient ranged from 0.34 to 0.74 based on dissimilarity matrix. The dendrogram grouped the genotypes into 3 main groups with group I and II having maximum number of genotypes. The pattern of genotype grouping into clusters was independent of their eco-geographical regions and gave a useful insight into their phylogenetic relationships. Analysis of molecular variance (AMOVA) indicated that maximum genetic diversity was partitioned within groups (84%) and only 16% of total variation occurred between the groups. The phylogenetic relationship was determined by principal co-ordinate analysis (PCoA) that explained 23.41% cumulative variance. PCoA revealed similar clustering pattern of genotypes along the axis, thereby corroborating the clustering of genotypes in UPGMA dendrogram.